Assessment of nutritional status in paediatric outpatients using bioelectrical impedance analysis and anthropometric z‐scores. (22nd March 2021) - Zhu, Yuan; Ye, Hong; Feng, Yi; Pan, Li‐ya; Fu, Huan‐huan; Liu, Yun‐man; Fei, Jun; Hong, Li
Abstract : Aim: To investigate paediatric outpatients' nutritional status using bioelectrical impedance analysis and anthropometric z ‐scores. Methods: A retrospective data analysis of tertiary paediatric hospital outpatients from 2017 to 2019 was conducted. Patients were categorised into three groups (non‐illness, illness and simple obesity) according to clinical diagnoses. The nutritional status was evaluated using anthropometric and bioelectrical impedance analysis. In addition, body composition measurements of patients in three subgroups of the illness group and age‐ and gender‐matched healthy controls were compared. Results: A total of 2015 paediatric outpatients were enrolled. According to body mass index z ‐scores, undernutrition prevalence among participants was 14.0% (non‐illness group, 21.3%; illness group, 11.4%). Body composition measurements indicated that 41.6% of participants had a low fat‐free mass index, and the proportions of participants with a low fat‐free mass index in the non‐illness, illness and simple obesity groups were 48.4, 47.0 and 10.7%, respectively. Compared with healthy controls, the haematology and oncology subgroup had a significantly lower fat‐free mass index and fat mass index; the nephrology and rheumatology subgroup had significantly lower height‐for‐age z ‐scores but higher fat mass index; and the gastroenterology subgroups had lower fat mass index, fat‐free mass index and body mass index z ‐scores. Conclusions: The results suggested the low fat‐free mass index prevalence was greater than the low body mass index z ‐score prevalence among paediatric outpatients, and body composition parameters varied across different illnesses. Body composition analysis is recommended in nutrition clinics for accurate paediatric outpatient nutritional assessment, thereby providing timely individualised nutritional interventions.